2016
DOI: 10.3389/fmicb.2016.01654
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of PknI-Rv2159c Interaction in Redox Homeostasis of Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis adapts to stress conditions by responding to the signals from its external environment. M. tuberculosis genome encodes 11 eukaryotic like serine/threonine protein kinases (STPK) and their importance in regulating the physiology and virulence of the bacteria are being explored. Previous study from our lab identified the M. tuberculosis STPK, PknI interacts with two peroxidase proteins such as Rv2159c and Rv0148. In this study, we have characterized the biological function behind the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…PknE, PknH, PknI and PknK, toghether with PknG, have important roles in Mtb intracellular survival [21,[79][80][81][82]. For instance, PknE has been demonstrated to promote the suppression of apoptosis, as shown by the use of a pknEdeleted Mtb strain [79,83], and to be involved in adaptive responses [84] and HIV co-infection [85]; PknH is implicated in Mtb dormancy [86] and in the regulation of cell wall biosynthesis [87], while PknI plays a role in the redox homeostasis during oxidative stress [88]. Moreover, advances in integrated proteomic approaches allowed to assign novel biological functions to the different STPKs.…”
Section: Others Mtb Stpksmentioning
confidence: 99%
“…PknE, PknH, PknI and PknK, toghether with PknG, have important roles in Mtb intracellular survival [21,[79][80][81][82]. For instance, PknE has been demonstrated to promote the suppression of apoptosis, as shown by the use of a pknEdeleted Mtb strain [79,83], and to be involved in adaptive responses [84] and HIV co-infection [85]; PknH is implicated in Mtb dormancy [86] and in the regulation of cell wall biosynthesis [87], while PknI plays a role in the redox homeostasis during oxidative stress [88]. Moreover, advances in integrated proteomic approaches allowed to assign novel biological functions to the different STPKs.…”
Section: Others Mtb Stpksmentioning
confidence: 99%
“…MshD involved in mycothiol (MSH) biosynthesis has a similar function to glutathione ( Newton et al, 2008 ). Mutations in mshD resulted in MSH production defect ( Newton et al, 2005 ; Venkatesan et al, 2016 ). An ahpC mutant Mtb showed decreased survival in macrophages ( Master et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rv2159c has also been reported to interact with Rv0148, a putative short chain dehydrogenase involved in intermediary metabolism, homeostasis, virulence, and drug resistance of M. tuberculosis [18,19]. Gene knockdown studies on Rv2159c report reduced in vitro survival of the bacteria and a higher level of sensitivity to oxidative stress, compared to the wild type strain [14]. These findings suggest that Rv2159c has a potential role in the virulence of M. tuberculosis.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, presence of cysteine residues at the catalytic site (Cys-Pro-Try-Cys) of Rv2159c contributes to peroxidase activity. Enzymatic assays of the catalytic site indicate that Cys84 is a key residue for alkylhydroperoxidase activity of Rv2159c [14]. A protein-BLAST analysis revealed that Rv2159c shares amino acid sequence identity with similar proteins in other mycobacterial species, including M. angelicum (100% identity) and M. riyadhense (79.4% identity).…”
Section: Introductionmentioning
confidence: 99%